Las herramientas de la reforma constitucional, la paradoja de la cláusula abierta o enmienda constitucional. - Murrillo Delgado, Jhoann Alexander (2023)
ABSTRACT: Constitutional reform is the instrument a constitution uses to adapt to the changes in the existing expectations in the social environment that requires it. On the other hand, constitutional amendment refers to the modification or change made to the Constitution; it allows to adjust or update of specific aspects of the fundamental norm without rewriting the text. The objective of the open clause is to ensure that human rights are applicable in changing contexts and that States are obliged to take measures to protect and promote human rights in all circumstances. The methodology within the present investigation is dogmatic and legally descriptive. Later, the researcher carried out an opinionated, legal- doctrinal, and descriptive legal analysis. The result of the study has allowed us to establish that the paradox between the constitutional amendment and the open clause exists. However, the effective method to guarantee and protect the rights of citizens without the need for a constitutional amendment is the available clause's direct, practical, and immediate application.